A research agenda on oral health care as a boundary object that unites the perspectives of patients and practitioners - Femke Hilverda; Puck van derWouden; Geert J. M. G. van derHeijden; Carina A. C. M. Pittens (Wiley, 2021)
Abstract Context A research agenda for oral health care was established in the Netherlands using the Dialogue Model. This project served as a case study in which we applied boundary‐work theory as a framework to understand boundaries (ie demarcations) between and within groups, and how these boundaries can be overcome. Objective To gain insights into the boundaries encountered when setting a research agenda, we analysed how this agenda served as a boundary object (ie circumstances, situations or material that connect actor groups and allow boundary crossing) that facilitated crossing boundaries and uniting the perspectives of patients and practitioners. Methods We used a thematic approach to analyse researchers' observations, meeting materials, emails, interviews with patients (n = 11) and a survey among patients and practitioners (n = 18). Results Setting the research agenda helped to cross boundaries in oral health care, which demonstrates its role as a boundary object. First, this made it possible to integrate research topics representing the perspectives and priorities of all patients and also to unite those perspectives. It was essential to involve practitioners at an early stage of the project so that they could better accept the patients' perspectives. This resulted in support for an integrated research agenda, which facilitated the crossing of boundaries. Conclusions The research agenda‐setting project was found to serve as a boundary object in uniting the perspectives and priorities of patients and practitioners. Patient contribution Patient involvement in this case study was structured in the process of research agenda setting using the Dialogue Model.